2006
DOI: 10.1007/s00125-006-0264-x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in human pregnancy: implications for regulation of glucose and lipid metabolism

Abstract: Aims/hypothesis: Adiponectin is upregulated during adipogenesis and downregulated in insulin-resistant states. The mechanism(s) governing the re-arrangements from adipogenesis to facilitated lipolysis during pregnancy are unknown. Our purpose was to analyse the role of adiponectin relative to the metabolic changes in human pregnancy. Subjects, materials and methods: Lean women (BMI <25 kg/m²) were evaluated longitudinally before conception, and in early (12-14 weeks) and late (34-36 weeks) pregnancy. Insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
211
6
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(250 citation statements)
references
References 51 publications
17
211
6
16
Order By: Relevance
“…Circulating levels may also reflect the contribution of subcutaneous adipose tissue expression, which for some adipokines, such as leptin, is significantly greater in subcutaneous fat than in visceral fat (10). Surprisingly, serum levels of adiponectin were unchanged in the three groups studied, which is in contrast to human studies that found adiponectin levels to be decreased in late gestation (6). This difference may be due to the adiponectin expressed in the rodent placenta and perhaps a species-specific difference in the amount that reaches the maternal compartment.…”
Section: Discussioncontrasting
confidence: 65%
“…Circulating levels may also reflect the contribution of subcutaneous adipose tissue expression, which for some adipokines, such as leptin, is significantly greater in subcutaneous fat than in visceral fat (10). Surprisingly, serum levels of adiponectin were unchanged in the three groups studied, which is in contrast to human studies that found adiponectin levels to be decreased in late gestation (6). This difference may be due to the adiponectin expressed in the rodent placenta and perhaps a species-specific difference in the amount that reaches the maternal compartment.…”
Section: Discussioncontrasting
confidence: 65%
“…Second, low adiponectin has been repeatedly associated with insulin resistance, consistent with the known insulin-sensitising bio-activity of the protein [8,11]. This inverse relationship between adiponectin and insulin resistance has also been consistently observed during pregnancy and in GDM [20,21,27]. Finally, a growing body of literature has recently queried a link between adiponectin and beta cell function, although conclusive resolution of this question remains elusive owing to some conflicting observations in this asyet modest literature.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study reported progressive decline in maternal adiponectin secretion during the course of pregnancy which was associated with a 60 % reduction in adiponectin mRNA in white adipose tissue [38]. Reduced adiponectin levels in second and third trimesters compared to first trimester in healthy pregnant subjects was reported by many authors [38,39], although others reported unchanged values [22,29]. In the present study, unchanged maternal circulating adiponectin in normal pregnancy between 2nd and 3rd trimesters may represent an independent protective mechanism against the gradual increase in insulin resistance.…”
Section: Discussionmentioning
confidence: 94%